Investigating the Impact of Student Participation in a Decentralised Virtual Laboratory on the Practical Learning of Open-Source Operating System at Politeknik Mukah (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
The decentralised virtual laboratory approaches are advantageous from an economic and administrative standpoint, and they have also been demonstrated to be a viable alternative for delivering practical learning, enhancing student achievement, and improving learning outcomes. Using the decentralised virtual laboratory approach, students can perform laboratory tasks on their own laptops or workstations at any time, location, and pace. Type-2 or hosted hypervisors are important virtualization technologies for the strategy because they allow several virtual machines to run concurrently on the host computer. Students participating in this study deploy Oracle VM VirtualBox, which is mostly hosted on Windows machines, to perform Linux administrative tasks or activities. A descriptive study of the students' post-responses leads to an investigation of their perspectives and acceptance of the approach. The primary factor that defines the effectiveness of the solution is the extent to which the approach helps students better comprehend the concept. This study concludes that the approach provides strong support for the hypothesis that participation in a decentralised virtual laboratory has a positive effect on students' perceptions of and motivation for hands-on learning. This method can continue to be adopted because it has a beneficial effect on students' decisions to continue their majors and study plans at Politeknik Mukah.